Letter from Marcus Benjamin to James Curtis Booth, June 16, 1886 - Benjamin, Marcus (1886)
Marcus Benjamin (1857-1932), an American chemist and editor, requests biographical information from James Curtis Booth (1810-1888) for use in Drake's Dictionary of American Biography (1872).
Keywords: Booth, James Curtis, 1810-1888; Benjamin, Marcus, 1857-1932